Insights into the Effects of the Dental Stem Cell Secretome on Nerve Regeneration: Towards Cell-Free Treatment - Rohaina Che Man; Nadiah Sulaiman; Ruszymah Bt Hj Idrus; Shahrul Hisham Zainal Ariffin; Rohaya Megat Abdul Wahab; Muhammad Dain Yazid (Hindawi Limited, 2019)
Cell-free treatment is emerging as an alternative to cell delivery to promote endogenous regeneration using cell-derived factors. The purpose of this article was to systematically review studies of the effects of the dental stem cell secretome on nerve regeneration. PubMed and Scopus databases were used where searched and related studies were selected. The primary search identified 36 articles with the utilized keywords; however, only 13 articles met the defined inclusion criteria. Eight out of thirteen articles included in vivo and in vitro studies. We classified the dental stem cell-derived secretome with its nerve regeneration potential. All studies demonstrated that dental stem cell-derived factors promote neurotrophic effects that can mechanistically stimulate nerve regeneration in neurodegenerative diseases and nerve injury. This data collection will enable researchers to gather information to create a precise formulation for future prescribed treatments.